September 11 and the U.S. war beyond the curtain of smoke (City Lights Books ; Freedom Voices Press, 2002)
This collection of essays by activists, journalists, historians, and political theorists outlines the U.S. policies that contributed to the tragedy of 9/11, the consequences of the new war, and suggestions for options and alternatives, such as grass-roots organizing linked to the anti-globalization movement and the strengthening of institutions like the International Criminal Court and the United Nations.